1990
DOI: 10.1038/clpt.1990.164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and gender on in vitro properties of human liver microsomal monooxygenases

Abstract: Aging in humans is associated with marked declines in the disposition of numerous drugs and other xenobiotics that require hepatic biotransformation before elimination. Considerable pharmacokinetic evidence in humans, coupled with data on in vitro liver microsomal monooxygenase functions generated in inbred male rodent models, has implicated impaired liver phase I drug metabolism (i.e., diminished efficacy of microsomal monooxygenases) in reduced drug clearance in the elderly. This study (1) assessed the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
1
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(101 citation statements)
references
References 0 publications
7
90
1
3
Order By: Relevance
“…Several lines of evidence indicate that the metabolism of several clinical drugs, mainly oxidized by CYP3A4, is more efficient in women than in men (Greenblatt et al, 1980;Watkins et al, 1989;Gorski et al, 1998). Recent studies show that women have higher hepatic CYP3A4 content and drug-metabolizing capacity than men (Wolbold et al, 2003); however, this conclusion is opposed by other observations (Schmucker et al, 1990;George et al, 1995).…”
contrasting
confidence: 52%
“…Several lines of evidence indicate that the metabolism of several clinical drugs, mainly oxidized by CYP3A4, is more efficient in women than in men (Greenblatt et al, 1980;Watkins et al, 1989;Gorski et al, 1998). Recent studies show that women have higher hepatic CYP3A4 content and drug-metabolizing capacity than men (Wolbold et al, 2003); however, this conclusion is opposed by other observations (Schmucker et al, 1990;George et al, 1995).…”
contrasting
confidence: 52%
“…A recent study of 94 surgical liver samples found 2-fold higher CYP3A4 protein content and higher expression of CYP3A4 mRNA transcripts in female compared with male samples (61). In contrast, other studies in human livers observed no sex differences in CYP3A (62,63). Regardless of apparent sex-related differences in CYP3A activity, the same range of wide interpatient variation in CYP3A activity was observed in both female and male cancer patients ( Table 4), indicating that dosing strategies for drugs cleared by CYP3A should focus on the individual and not necessarily sex.…”
Section: Discussionmentioning
confidence: 75%
“…The increase in CYP3A4 catalytic activity observed in confluent Huh7 cells can be explained by the concomitant and time-dependent increase of CYP3A4 and its electron donor POR. It is believed that under certain conditions, POR can be the rate-limiting factor for P450 activity, because the POR protein is expressed at much lower stoichiometric amounts than the P450s in the liver (Schmucker et al, 1990). Like POR, CYB5A, another well known modulator of CYP3A4 activity (Gan et al, 2009), also gradually increased with time of confluence, although it could not be detected until 3 weeks of confluence.…”
Section: Discussionmentioning
confidence: 99%